Early Passive Leg Movement Prevents Against the Development of Heart Failure With Preserved Ejection Fraction in Rats - Liu, Jian; Ji, Xi-xin; Fu, Yang; Zhang, Wen-chao; Ji, Hui-fang; Liu, Jian-wei; Cheng, Xiao-shu; Dong, Yi-Fei (Frontiers in Cardiovascular Medicine, 2021)
Previous studies reported that exercising brought great benefits to the heart failure with perserved ejection fraction (HFpEF), which reduced the hospitalization and the mortality of heart failure. However, the underlying mechanism of exercising on HFpEF remains unclear. In the present study, we designed and constructed a device that can perform early passive leg movement (ePLM) in rats and further observed whether pretreatment of ePLM exerts protective effects on HFpEF of rats. Rats were fed with high salt feed to establish an animal model of pre-clinical diastolic dysfunction (PDD), which would eventually develop into HFpEF, and then pretreated rats with ePLM. We conducted several experiments to evaluate the conditions of heart and vascular endothelium tissues. The results show that diastolic functions of heart and vascular endothelium in rats were significantly improved by pretreatment of ePLM. We also found that pathological injuries of heart and vascular endothelium were ameliorated after pretreatment of ePLM. Moreover, pretreatment of ePLM decreased the protein levels of Collagen type I, Collagen type Ⅲ, MMP2 and MMP9 in heart and vascular endothelium tissues, indicating that cardiac and vascular fibrosis were reduced apparently by pretreatment of ePLM. Further investigation suggested that pretreatment of ePLM probably inhibit the activation of TGF-β1/Smad3 signaling pathway as well as promote the activation of Akt/eNOS signaling pathway in high salt diet induced HFpEF. In conclusion, pretreatment of ePLM alleviated high salt diet induced HFpEF by inhibiting fibrosis via suppressing TGF-β1/Smad3 signaling pathway as well as activating Akt/eNOS signaling pathway, implicating pretreatment of ePLM as a promising non-medicine therapeutic approach for treating HFpEF.